Thirteen steps down : a novel - Rendell, Ruth, 1930- (New York : Crown Publishers, 2005)
Elderly Gwendolyn Chawcer and her colorful group of friends become increasingly suspicious of her tenant, Michael "Mix" Cellini, an eccentric who idolizes serial killer Reggie Christie, as his odd behavior take an ever darker turn.
Keywords: Murderers -- Fiction; Serial murders -- Fiction; Landlord and tenant -- Fiction; Psychological fiction; Suspense fiction